Knowledge and attitudes towards addiction to psychoactive substances inprofessional groups of health care workers, teachers and the police in the Lubuskie Voivodeship - Chmielowiec, Jolanta; Grzywacz, Elżbieta; Grzymkowska, Maria; Chwałczyńska, Justyna; Błaszczak, Katarzyna; Masiak, Jolanta; Chmielowiec, Krzysztof (Current Problems of Psychiatry, 2022)
Drug addiction is a common phenomenon that increases with the progress of the European integration process. Professional help to people addicted and under the influence of drugs or other psychoactive substances should be provided primarily by health care institutions. An important and interesting issue seems to be the assessment of how people who have the most frequent contact with addicts are prepared to provide help, what is their knowledge and attitude to the phenomenon of drug addiction and to people addicted to psychoactive substances. The material for the research was a questionnaire for people who have contact and / or work professionally with people addicted to psychoactive substances. A total number of 253 people who had professional contact with people addicted to psychoactive substances were examined, including 102 men and 151 women. The respondents most often acquired knowledge in the field of drug addiction through the mass media. The exception is the professional group of doctors, which was the only one to refer to professional literature. Contact with drug addicts was not worried by 68.6% of doctors, 68.4% of policemen, 45.9% of nurses and only 39.0% of teachers. Fear may be caused mainly by possible aggressive behavior, which is feared by 49.8% of the respondents, including 58.3% of women and 37.2% of men. When it comes to 90.1% of respondents, they believe that the cause of aggression is the lack of control over their emotions. The results of the work can be helpful in creating new, satisfying solutions to difficult situations and developing cooperation characterized by empathy and acceptance.